Cloning and DNA sequence of the omc gene encoding the outer membrane protein-macromolecular complex from Neisseria gonorrhoeae. - Tsai, W M (1989)
The omc gene, encoding the outer membrane protein-macromolecular complex (OMP-MC), was cloned in two pieces from Neisseria gonorrhoeae 2686. The 5' fragment of the omc gene included a promoter sequence, as indicated by its unregulated expression in Escherichia coli. Attempts to reconstruct an intact omc gene were unsuccessful, suggesting that expression of the complete OMP-MC protein was toxic to E. coli. Complete sequence determination revealed a coding sequence of 2,133 nucleotides; the deduced amino acid sequence indicated a mature protein of 687 amino acids with an NH2-terminal signal peptide of 24 amino acids. Analysis of the deduced amino acid sequence revealed that the NH2-terminal half of OMP-MC is generally hydrophilic, while the COOH-terminal portion contains alternating hydrophobic and hydrophilic regions. Serological analyses demonstrated that the NH2-terminal portion of OMP-MC is exposed on the gonococcal surface and the COOH-terminal portion is membrane associated.